PENGARUH JOB INVOLVEMENT TERHADAP JOB PERFORMANCE DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. WAHANA LENTERA RAYA GRESIK - SETYANI, DELLA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Companies as a form of organization should be aware of the importance of employees as the executive and the resources that affect the progress of the company. Job involvement is important for employeeâ€™s job performance to increase the companyâ€™s advanced. Organizational citizenship behavior is a â€œlubricantâ€ in the social machinery of organizations that can improve companyâ€™s performance. This study aims to examine the effect of job involvement on job performance and organizational citizenship behavior on the employees of PT. Wahana Lentera Raya Gresik. In this research used conclusive research in the form of survey research. Sampling technique used was non-probability sampling. Type of method used was purposive sampling. The sample used amounted to 150 employees of PT. Wahana Lentera Raya Gresik. Data were collected using a questionnaire. Analytical techniques used are structural equation modeling. The results of this analysis indicate that job involvement has a positive and significant impact on job performance, job involvement addition has a positive and significant impact on organizational citizenship behavior. And organizational citizenship behavior has a positive and significant impact on job performance. Keywords: Job Involvement, Job Performance, and Organizational Citizenship Behavior